2017
DOI: 10.1039/c7py00219j
|View full text |Cite
|
Sign up to set email alerts
|

The hydrolytic behavior of N,N′-(dimethylamino)ethyl acrylate-functionalized polymeric stars

Abstract: Well-defined N,N′-(dimethylamino)ethyl acrylate (DMAEA) functionalized polymeric stars have been synthesized via an arm-first approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 46 publications
(72 reference statements)
4
18
0
Order By: Relevance
“…Clearly, the stability of the ester moiety of the polymethacrylates, which is attached directly to the backbone, is much higher than the one reported for ester moieties placed in the side chains of methacrylic polymers well separated from the backbone [62,63,64]. This remarkable finding goes along with previous reports that polymethacrylates are much less sensitive to hydrolysis than their polyacrylate analogs [32,33,34,35,37]. This may be explained by steric effects.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…Clearly, the stability of the ester moiety of the polymethacrylates, which is attached directly to the backbone, is much higher than the one reported for ester moieties placed in the side chains of methacrylic polymers well separated from the backbone [62,63,64]. This remarkable finding goes along with previous reports that polymethacrylates are much less sensitive to hydrolysis than their polyacrylate analogs [32,33,34,35,37]. This may be explained by steric effects.…”
Section: Resultsmentioning
confidence: 52%
“…Accordingly, the literature assessments of the stability of antifouling polymers often represent mere assumptions, or are based on singular observations for which the precise experimental conditions are often not disclosed. According to the data available, polyacrylates seem to be rather susceptible to hydrolysis, much more than polymethacrylates [32,33,34,35,36,37]. Moreover, for the case of the monomers, methacrylamides were shown to resist hydrolysis better than methacrylates do [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Release must occur to allow the dsRNA to become available so to trigger RNAi . Considerable efforts have been directed at overcoming this problem, in particular, poly­(2-(dimethylamino)­ethyl acrylate) (PDMAEA) has been reported as having a self-catalyzed hydrolysis property, with autodegradation to poly­(acrylic acid) and 2-(dimethylamino)­ethanol when in aqueous solution. In addition, PDMAEA has a high transfection efficiency into HeLa cells when complexed with RNA, can facilitate complete release of RNA and exhibits very low toxicity. , We thus envisaged that PDMAEA could be a good candidate to protect the dsRNA in soil and delay degradation prior to release.…”
mentioning
confidence: 99%
“…These results indicated that the alkalinee nvironmentp roduced by the tertiarya mine group could accelerate the ester bond cleavage in water;h owever,t his effect was weakened in PBS. For compound 1a under different amountso fH 2 O 2 in PBS (pH 7.4), we found that the charger eversal rates were similar andt he final zeta potentialw ere all around À6mV ( Figure 1d;s ee the Supporting Information, Figure S31), which indicates that the ultrafast cleavage of the ester bond in compound 1a was little affected by the concentrationo fs timulis ignals and was only related to the formationo ft he HBC structure.O nt he basis of these results, it could be found that the ester hydrolysis rate in compound 1a and b was not only much faster than the methods reported, [14,22,25,29,35] which created an alkaline environment by using the tertiarya mines residues,b ut was also much faster than b-thiopropionate esters, which are acid-sensitive. [30,31] Dynamics of the ester bond hydrolysis in compounds1 -3…”
Section: Chargea Lteration Of Compounds 1-3mentioning
confidence: 78%